Causes of Unionization in Canadian Banks - Lowe, Graham (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
This paper investigates the origins and development of unions in the Canadian banking industry since 1976. The historically low level of unionization in banking, coupled with its largely female workforce, makes bank unionization a significant development on the Canadian industrial relations scène.